2019
DOI: 10.1002/anie.201907679
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing Progressive Atomic Change in the Metal Surface Structure Made by Ultrafast Electronic Interactions in an Ambient Environment

Abstract: Understanding the atomic and molecular phenomena occurring in working catalysts and nanodevices requires the elucidation of atomic migration originating from electronic excitations.The progressive atomic dynamics on metal surface under controlled electronic stimulus in real time,space,and gas environments are visualizedf or the first time.B yi nsitu environmental transmission electron microscopy, the gas molecules introduced into the biased metal nanogap could be activated by electron tunneling and caused the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…A well-known problem for nanogap production is the so called electric migration, where metal atoms of the nanogap electrode migrate in the electric field in line with the flowing current, leading to a merging event of the confining walls. 136 Naitoh et al used electronic migration to form 2 nm gaps between Au electrodes. 130 They observed the gap shrinkage by measuring the transferred current between both electrodes as conductivity strongly increases with decreasing electrode distance.…”
Section: Sub-nm Effects In Electrochemical Confinementmentioning
confidence: 99%
“…A well-known problem for nanogap production is the so called electric migration, where metal atoms of the nanogap electrode migrate in the electric field in line with the flowing current, leading to a merging event of the confining walls. 136 Naitoh et al used electronic migration to form 2 nm gaps between Au electrodes. 130 They observed the gap shrinkage by measuring the transferred current between both electrodes as conductivity strongly increases with decreasing electrode distance.…”
Section: Sub-nm Effects In Electrochemical Confinementmentioning
confidence: 99%
“…Despite those remarkable advances, however, direct observation of surface reactivity and structural reconstruction on terminations of GBs remains a forbidden challenge, which is crucial for the GBs engineering in catalysis. With a state-of-the-art spatial resolution, in situ aberration-corrected transmission electron microscopy (AC-TEM) has shown the power for studies of nanocrystal growth, , nanoparticles (NPs) restructuring under gas environments, , catalysis, , and so on.…”
mentioning
confidence: 99%
“…We have investigated atomic structures and dynamics of nanomaterials under reaction conditions by ETEM while taking into account the effects of electron irradiation [2][3][4][5][6][7]. We have found that the surface of Pt nanoparticles is oxidized in O2 gas under electron irradiation ( Figure 1).…”
mentioning
confidence: 99%